ASSOCIATION BETWEEN EMOTIONAL VARIABLES AND DISEASE ACTIVITY PARAMETERS IN PATIENTS WITH RHEUMATOID ARTHRITIS - Meltem Sayın; Mehmet Eryılmaz; Nehir Samancı; Tiraje Tuncer (Archives of Rheumatology, 2001)
It is thought that the emotional status of the patients has an important role in both the etiopathogenesis and the prognosis of the rheumatoid arthritis. The aim of the study is to investigate the association between the disease activity parameters and the emotional variables. A total of 23 patients (19 female, 4 male) were included in the study. Mean age of the patients 46,16± 13,26. The mean duration of disease was 143,58 ± 105,97 months. There was not any correlation between the emotional variables and the parameters such as age, duration of disease, morning stiffness, HAQ, grip strength, ESR,CRP and leucocyte. There was a significant correlation between joint swelling score and Hamilton Depression and State Anxiety Inventory; between joint tenderness score and the scores of State Anxiety Inventory; between VAS and Hamilton Anxiety and State Anxiety Inventory. There was a positive correlation between walking time and State Anxiety Inventory. This study shows that patients with rheumatoid arthritis do not display an obuiours depression and anxiety disorder. However, it was seen that the instantaneous anxiety of the patients and their joint tenderness, swelling and pain perception affected each other. Therefore during follow up of these patients, not only the physical parameters, but emotional parameters should also be considered and this may affect the success of the treatment positively.